Beak and skull shapes of human commensal and non-commensal house sparrows Passer domesticus - Riyahi, Sepand; Hammer, Øyvind; Arbabi, Tayebeh; Sánchez, Antonio; Roselaar, Cees S.; Aliabadian, Mansour; Sætre, Glenn-Peter (BMC evolutionary biology, 2013)
The granivorous house sparrow Passer domesticus is thought to have developed its commensal relationship with humans with the rise of agriculture in the Middle East some 10,000 years ago, and to have expanded with the spread of agriculture in Eurasia during the last few thousand years. One subspecies, P. d. bactrianus, residing in Central Asia, has apparently maintained the ancestral ecology, however. This subspecies is not associated with human settlements; it is migratory and lives in natural grass- and wetland habitats feeding on wild grass seeds. It is well documented that the agricultural revolution was associated with an increase in grain size and changes in seed structure in cultivated cereals, the preferred food source of commensal house sparrow. Accordingly, we hypothesize that correlated changes may have occurred in beak and skull morphology as adaptive responses to the change in diet. Here, we test this hypothesis by comparing the skull shapes of 101 house sparrows from Iran, belonging to five different subspecies, including the non-commensal P. d. bactrianus, using geometric morphometrics.
Gesehen am 14.01.2022